Pengaruh Pemberian Biochar Arang dan Pupuk Kandang Ayam terhadap pH, Ktk, C, K Tanah dan Pertumbuhan serta Produksi Tanaman Cabai Merah (Capsium Annum L.) pada Tanah Ultisol - Minarti, Minarti; Ginting, Sahta; Rembon, Fransiscus S; Darwis, Darwis; Resman, Resman; Namriah, Namriah (CV. Eduartpia Publisher, 2023)
This study aims to understand the effects of biocharcoal and manure interactions on pH, CEC, C, K soils and the growth and production of red pepper plants on ultisol soils and to understand the independent effects of biocharcoal charcoal and chicken manure on pH, CEC K, C, K soils and growth and production The red chili pepper plant in the soil of the ultisol. This study used the Randomized Group Design (RDB) in factorial patterns. The first factor, Biocharanganese consists of three levels: B0 = without the addition of biocharangium B1 = 300 g polybag-1 B2 = 600 g polybag-1 The second factor is that chicken manure consists of 3 levels, namely A0= without giving chicken manure, A1=100g polybag-1, A2=200g polybag-1. Research results show that the delivery of biocharcoal and chicken manure can improve the chemical properties of pH, CEC, organic-c except available-k are available and have no effect on the growth and production of red chili peppers while for the growth and production of red chili peppers only self-supplying chicken manure has a better effect on the plant height, number of branches, number of fruit and weight at 200 g of polybag-1 (A2).Keywords: soil chemistry, charcoal biocharcoal, chicken manure, red pepper, Ultisol